A Bacterial Parasite Effector Mediates Insect Vector Attraction in Host Plants Independently of Developmental Changes - Orlovskis, Zigmunds; Hogenhout, Saskia A. (Frontiers in Plant Science, 2016)
Parasites can take over their hosts and trigger dramatic changes in host appearance and behaviour that are typically interpreted as extended phenotypes to promote parasite survival and fitness. For example, Toxoplasma gondii manipulates the behaviour of infected rodents to aid transmission to cats and parasitic trematodes of the genus Ribeiroia alter limb development in its amphibian host to facilitate predation of this intermediate host by birds. Plant parasites and pathogens also reprogram host development and morphology. Phytoplasma parasites of plants induce extensive leaf-like flower phenotypes (phyllody) in their host plants, presumably to attract insect vectors on which these bacteria depend for transmission. However, it remains debatable whether morphological phenotypes, such as phyllody, are directly beneficial to the parasites or are side-products of parasite infection. Previously, we found that phytoplasma virulence protein (effector) SAP54 binds and mediates degradation of host MADS-box transcription factors (MTFs), regulatory hubs of plant development and hormone physiology, to induce phyllody and promote insect vector colonisation. Here we show that plants heterologously expressing SAP54 are strongly attractive to insects, but surprisingly, insect attraction was independent of the presence of leaf-like flowers. Moreover, plants that produce leaf-like flowers in the absence of SAP54 did not attract insects. We conclude that the SAP54 effector mediates insect vector attraction in host plants by exploiting the role of its MTF targets in insect defence and that perturbation of floral development may be a secondary effect of the effector activity.